Using the ovsynch protocol for prompt re-insemination of cows diagnosed open at pregnancy checks - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1999)
Using the Ovsynch protocol to prepare cows for re-insemination proved to be very effective. Its use guarantees that all cows found open at pregnancy diagnosis are reinseminated promptly within 10 days, and the average pregnancy rate of 28.7% in 136 cows was acceptable. Pregnancy rates were not different whether or not estrus was detected in cows at the timed insemination, but they tended to be greater at second services compared to other repeat services. The Ovsynch protocol is an effective tool to use to ensure prompt re-insemination of open cows.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Ovsynch protocol; Open cows